Cytotoxic activity of immune cells following administration of xenogeneic cancer vaccine in mice with melanoma B-16 - Fedosova, N.I.; Voeykova, I.M.; Karaman, O.M.; Symchych, T.V.; Didenko, G.V.; Lisovenko, G.S.; Evstratieva, L.M.; Potebnya, G.P. (Experimental Oncology, 2015)
Aim: To study the effects of xenogeneic cancer vaccine (XCV) developed on the basis of nervous tissue antigen from rat embryo of late gestation period and protein-containing metabolite of Bacillus subtilis with molecular weight of 70 kDa, on specific and unspecific antitumor reactions of cellular and humoral chains of immune system, and to analyze possible mechanisms of its antimetastatic action. Materials and Methods: XCV was administered triply with 3-day intervals after surgical removal of experimental melanoma В-16 in C57Bl/6 mice. Cytotoxic activity (CTA) of splenocytes against target cells К-562 as well as CTA of splenocytes, peritoneal macrophages (PM) and blood serum against melanoma В-16 target cells were determined using МТТ test. The content of circulating immune complexes (CIC) in blood serum was evaluated by precipitation reaction. Results: Immunologic effects of XCV vaccination in experimental animals with surgically removed melanoma B-16 in comparison with similarly treated unvaccinated mice were as follows: prevention of medium molecular weight CIC accumulation in blood serum during all observation period, significant increase (р < 0.05) of CTA of effectors of unspecific antitumor immunity (natural killer cells — NK — by 25.5 ± 1.7 vs 12.5 ± 5.4%, and PM — by 37.3 ± 0.6 vs 32.0 ± 0.9%, respectively) at 37th day after the surgery, and also preservation of functional activity of specific cytotoxic lymphocytes at the level of intact control. Conclusion: The results of the study allow propose that antimetastatic effect of XCV vaccination could be based on increased CTA of NK and PM, and preservation of CTL functional activity at late terms after surgical removal of B-16 primary tumors. Key Words: xenogeneic cancer vaccine, melanoma В-16, natural killer cells, macrophages, cytotoxic lymphocytes, cytotoxic activity, antimetastatic activity.